The World English Bible (WEB): Judges - Anonymous (Salt Lake City, UT : Project Gutenberg, 2005)
"The World English Bible (WEB): Judges" by Anonymous is a biblical text that forms part of the Old Testament, likely written in ancient times around the early 1st millennium BC. This book details the period in Israel's history during which leaders known as judges arose to govern the people after the death of Joshua, highlighting themes of defeat, deliverance, and cycles of sin amongst the Israelites. Notable figures throughout include Ehud, Deborah, Jepthah, and Samson, each displaying both human flaws and divine favor. The opening of the text introduces the Israelites grappling with the aftermath of Joshua's death. They seek guidance from God on how to confront the Canaanites, receiving instructions to lead their conquests through the tribe of Judah. The narrative recounts the initial battles, including the notable defeat of the Canaanite leader Adoni-Bezek and the establishment of the tribe's dominance over various cities, setting the stage for the recurring themes of struggle and faithfulness that typify the Book of Judges. As the Israelites engage in battles, their disobedience leads to suffering and an ongoing need for divine intervention, which God provides through the judges who rise to lead them against their oppressors. (This is an automatically generated summary.)
Release date is 2005-06-01
From www.ebible.org with slight reformatting by Martin Ward
Keywords: Bible. Judges